Multimodal analysis of neural signals related to source memory encoding in young children - Yuqing Lei; John Richards; Fengji Geng; Tracy Riggins (Developmental Cognitive Neuroscience)
The emergence of source memory is an important milestone during memory development. Decades of research has explored neural correlates of source memory using electroencephalography (EEG) and functional magnetic resonance imaging (fMRI). However, connections between findings from the two approaches, particularly within children, remain unclear. This study identified fMRI-informed cortical sources of two EEG signals during memory encoding, the P2 and the late slow wave (LSW), that predicted subsequent source memory performance in a sample of children aged 4 to 8 years. Both P2 and LSW were source localized to cortical areas of the medial temporal lobe (MTL), reflecting MTL’s crucial role in both early-stage information processing and late-stage integration of memory, and validating LSW’s suspected role in memory updating. The P2 effect was localized to all six tested subregions of cortical MTL in both left and right hemispheres, whereas the LSW effect was only localized to the parahippocampal cortex and entorhinal cortex. P2 was additionally localized to multiple areas in the frontoparietal network, suggesting interactions between memory encoding and other cognitive functions. These results reflect the importance and potential of considering both spatial and temporal aspects of neural activity to decode memory mechanisms, paving the way for future developmental research.